Determinants of Working Environment and their Influence on Job Satisfaction: Evidence from Banking Sector - Mumtaz Ali Junejo; Muhammad Ashraf; Saifullah Shaikh (International Journal of Experiential Learning & Case Studies)
In today’s competitive market arena, human capital has been considered most significant factor to win the competitive edge. Thus, their attitude while on work has always added value to the organizational productivity. To tackle the competitive forces, most of the organizations have started working on creating satisfied working environment for employees. This study has therefore beenundertaken to explore the influence ofworkplace environment on satisfaction with job, of employees working in selected banks in Karachi. The subjects of interest were 230 bankers engaged in selected commercial banks in Karachi, Pakistan. However,200 duly filled responses were returned and found as useable for further analysis. The data was statistically analyzed through SPSS 20. The multiple linear regression and Pearson correlation were performed to test the hypotheses of this study. The results show that workplace environment effect immensely on satisfaction level of the employees. Most bankers in various banks were satisfied with working environment they had in their respected banks. All the hypotheses for this study were retained owing to significant influence of working environment on level of job satisfaction of bankers.